SCREENING FOR ATRIAL FIBRILLATION WITH ROUTINE AUTOMATED BLOOD PRESSURE MEASUREMENT IN THE ELDERLY: THE NATIONAL HEALTH SURVEY EMENO IN GREECE. (June 2022) - Stergiou, George S.; Menti, Ariadni; Kalpourtzi, Natasa; Gavana, Magda; Vantarakis, Apostolos; Chlouverakis, Gregory; Hadjichristodoulou, Christos; Trypsianis, Gregory; Voulgari, Paraskevi; Alamanos, Yannis; Karakosta, Argiro; Touloumi, Giota
Abstract : Objective: Atrial fibrillation (AF) is the most common sustained arrhythmia which often is asymptomatic and undiagnosed. An automated blood pressure (BP) monitor with an algorithm which detects atrial fibrillation with high diagnostic accuracy during routine measurement was used for AF screening in the elderly general population Greece. Design and method: EMENO health survey (2013 to 2016) applied a multi-stage stratified random sampling method to select a random sample of the general adult (> = 18 years) population of Greece. For participants aged > = 65 years screening for AF was performed with triplicate automated BP measurements using a validated automated upper-arm cuff oscillometric device with embedded algorithm for detecting AF (Microlife BPA100 Plus AFIB). Results: A total of 1, 838 individuals aged > = 65 years were recruited and 975 with AF data on at least 1 BP measurement were analysed (mean [SD] age 75.3 (6.6)) years, men 45.1%, BMI 30.3 (5.2) kg/m 2, hypertensives 80.7%). Of them, 65 (7.1%) had AF detected in all their 3 BP readings (AF group), 661 (69.5%) have no AF in all 3 readings (no AF group), and 249 (23.4%) had AF in 1 or 2 readings (uncertain AF group). Participants with AF were older than non-AF (by 3.4 years on average, p < 0.001), had lower systolic BP (by 4.6 mmHg, p < 0.05), and more frequent cardiovascular disease (29% vs 14%, p < 0.01). Among AF patients, 43% reported a previous AF diagnosis compared to 8.8% and 11.9% in no AF and uncertain AF group respectively (p < 0.001). Hypertension tended to be more common in the AF than the non-AF group (88% vs. 80%, p = NS). Of the 65 AF group, 57% were undiagnosed and all required anticoagulant therapy (men with CHA2DS2-VASc > = 1 or women > = 2). Conclusions: Almost 7% of people aged > = 65 years in Greece had AF detected during routine automated BP measurement. 57% of them were undiagnosed and all required anticoagulant treatment for stroke prevention. Screening for AF using routing automated BP measurement in the elderly appears to be a useful method for early detection and management of asymptomatic AF.